Adaptation Modes in Indonesian Subtitle of Enola Holmes (2020) Movie - Alika Kamilia Basar; Ida Zuraida (Budapest International Research and Critics University, 2022)
Movie is the most popular entertainment medium, which is liked and enjoyed by the majority of people around the world. Since a lot of movies are produced in one language but watched by people who speak in different languages, subtitle becomes the important way of conveying the utterances in the movie. However, literal translation is not possible in subtitling because of the differences in the sociocultural aspects and language structure. Therefore, the oblique translation technique is often used in the subtitling, consisting of transposition, modulation, equivalence, and adaptation. This study aims to examine adaptation modes applied in Indonesian subtitle of Enola Holmes (2020) movie using the qualitative descriptive comparative method. Data collection was performed by collecting data from the movie broadcasted by Netflix. Data analysis is carried out by comparing the Indonesian subtitle with the utterance using the data analysis technique by Krippendorff and Nazir. As the result, seven adaptation modes by Baker and Saldahan were applied in the translated subtitle. The frequency of applied adaptation mode consists of 14 times of Transcription of Original, 4 times of Omission, 2 times of Expansion, 14 times of Exoticism, 5 times of Updating, 11 times of Situational or Cultural Adequacy, and 1 time of Creation. The finding of the study indicates that adaptation modes can be applied when translating utterance to text.